Implementastion of Internal Inventory Merchandise Control System - Dita Andhini Setiyowati; Dwi Anggarani; Endah Puspitosarie (Optima Science, 2023)
Internal control is a security measure to prevent damage, theft or other irregularities. The formulation of the problem in this research is